BURNOUT SYNDROME IN MEDICAL STUDENTS - Deggerone, Indiamara; Machado Kramel, Amanda; Feier, Gustavo; Almeida Morais, Fábio; Pereira, Larissa; Madeira, Kristian (Cadernos ESP, 2021)
INTRODUCTION: Burnout is a syndrome characterized by emotional exhaustion, depersonalization and reduced personal fulfillment. It is a pathology that affects professionals and academics who have intense direct contact with people. Medicine is a particularly risky area for the development of Burnout due to its demanding characteristics, strenuous hours of study and little leisure time. OBJECTIVE: Verify the syndrome in medical students in a college that uses a methodology Problem Basead Learning(PBL) and, theprofile of the affected subjects including signs and symptoms. METHOD: Students of University of the Extreme South of Santa Catarina, (UNESC) were interviewed from the first to the last semester of medical school at college in thefirst week of class and end of semester, usingself-assessment questionnaires. RESULTS: An association was identified between the three dimensions of the Burnout syndrome, mainly in students of phases 3 (16.0%); 6 (12.0%) and 7 (12.0%) of the course, and that the prevalence was 14.4% at the beginning of classes and 20.6% at the end of the semester. CONCLUSION: Our results suggest that students who are in the first stages of the course have a higher risk of developing Burnout, and this intensifies at the end of the semester.
Keywords: Burnout; Medicine; Students